2016
DOI: 10.1111/jace.14547
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence for A‐Site Order in Perovskites

Abstract: Models for composition–structure relationships are useful in both the lab and industry, yet few exist for perovskites-containing extrinsic defects or cation ordering. In this work, an empirical model is used to predict the existence of A-site cation ordering. Specifically, four compositions in the Na(1−3x)/2La(1+x)/2TiO3 system (x = 0.0, 0.0533, 0.1733 and 0.225) were synthesized using a conventional solid-state mixed-oxide method. The structure of the x=0 end-member (Na0.5La0.5TiO3) has been reported in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…The ordering of cations on either A or B sites in a complex perovskite clearly has structural implications. It has also recently been established using this model and verified via both density functional theory (DFT) and Rietveld refinements that, while rock salt ordering of the B site results in a decrease in the unit‐cell volume with respect to the disordered state, A‐site layered ordering can result in an increase in the unit‐cell volume. This counterintuitive expansion was later explained crystalochemically by the fact that ordering in perovskites causes more efficient packing—and so shrinkage— within ordered planes but an expansion of bonds perpendicular to them.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…The ordering of cations on either A or B sites in a complex perovskite clearly has structural implications. It has also recently been established using this model and verified via both density functional theory (DFT) and Rietveld refinements that, while rock salt ordering of the B site results in a decrease in the unit‐cell volume with respect to the disordered state, A‐site layered ordering can result in an increase in the unit‐cell volume. This counterintuitive expansion was later explained crystalochemically by the fact that ordering in perovskites causes more efficient packing—and so shrinkage— within ordered planes but an expansion of bonds perpendicular to them.…”
Section: Introductionmentioning
confidence: 86%
“…In addition, the x = 0.2233 composition showed similar ordering. Knapp and Woodward also studied Na 0.5 La 0.5 TiO 3 ( x = 0) and observed no long‐range cation ordering on the A site; however, the NLT system was recently re‐examined by Tolman et al using electron diffraction, and short‐range cation ordering was observed for x = 0 and attributed to the existence of ordered nanodomains, which explains why the ordering is not observed via X‐ray diffraction (XRD). Furthermore, both (Na 0.5 La 0.5 )TiO 3 and (Na 0.5 Tb 0.5 )TiO 3 were later studied via neutron diffraction; and while the latter was observed in orthorhombic space group Pbnm , the former crystallized in trigonal space group R true3false¯ c .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, bonds which lie in or near the ordering planes will contract whereas those more perpendicular will tend to expand. For this reason, a strong indicator of rock salt B‐site ordering within this model is an overestimation of B‐X bond length, which results in large positive errors (1%‐3%) in both apc and apc. In these cases, a negative Δ r B correction term can be introduced to effectively correct for these errors.…”
Section: Introductionmentioning
confidence: 99%